2019
DOI: 10.1186/s13045-019-0793-7
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A1 in lung adenocarcinoma as a promising target of chimeric antigen receptor T cells

Abstract: BackgroundCancer/testis antigens (CTAs) are a special type of tumor antigen and are believed to act as potential targets for cancer immunotherapy.MethodsIn this study, we first screened a rational CTA MAGE-A1 for lung adenocarcinoma (LUAD) and explored the detailed characteristics of MAGE-A1 in LUAD development through a series of phenotypic experiments. Then, we developed a novel MAGE-A1-CAR-T cell (mCART) using lentiviral vector based on our previous MAGE-A1-scFv. The anti-tumor effects of this mCART were fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Other, more well-described, CT antigens have been tested as potential CAR targets. MAGE-A1 was investigated as a possible target in the treatment of lung adenocarcinoma (LUAD) after immunostaining revealed a surface epitope of the antigen ( 37 ). A MAGE-A1-specific CAR showed cytotoxic activity both in vitro and in vivo , where it was able to infiltrate MAGE-A1-positive tumors and specifically target and inhibit LUAD xenograft growth in nude mice.…”
Section: Cancer/testis Antigens As Targets For Car T-cell Therapymentioning
confidence: 99%
“…Other, more well-described, CT antigens have been tested as potential CAR targets. MAGE-A1 was investigated as a possible target in the treatment of lung adenocarcinoma (LUAD) after immunostaining revealed a surface epitope of the antigen ( 37 ). A MAGE-A1-specific CAR showed cytotoxic activity both in vitro and in vivo , where it was able to infiltrate MAGE-A1-positive tumors and specifically target and inhibit LUAD xenograft growth in nude mice.…”
Section: Cancer/testis Antigens As Targets For Car T-cell Therapymentioning
confidence: 99%
“…Its expression has also been associated with progression and survival in NSCLC, but the specific mechanism for this phenomenon remains unknown [ 45 , 46 ]. CT antigens are ideal targets for cancer immunotherapy, and MAGEA1 has been shown to be actionable in vitro and in vivo by chimeric antigen receptor (CAR) T-cell therapy in lung adenocarcinoma cells, where the lung adenocarcinoma cells were effectively destroyed by IFN-γ secretion due to MAGEA1 inhibition [ 47 ]. Thayaparan et al reported that treatment of MET -expressing malignant mesothelioma cells with MET-retargeted CAR T cells was associated with significant IFN-γ release and tumor cell destruction [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although various cancers demonstrate MAGE-A family gene overexpression and the accumulation of their encoded proteins [19][20][21][22][23][24][25][26][27][28], the specific MAGE-A gene products that…”
Section: Discussionmentioning
confidence: 99%
“…Although various cancers demonstrate MAGE-A family gene overexpression and the accumulation of their encoded proteins [19][20][21][22][23][24][25][26][27][28], the specific MAGE-A gene products that are functionally relevant in breast cancer remain largely undetermined. To address this, we first analyzed the RNA-seq data of 70 breast cancer cell lines to determine the breast-cancer-related expression patterns of the MAGE-A gene family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation